2003
DOI: 10.1086/367791
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of the Optical and X-Ray Emission from Scorpius X-1

Abstract: In 1970, Hiltner & Mook reported the results of the first multiyear study of the optical emission from Sco X-1. They found that the Sco X-1 B-magnitude histograms changed from year to year. Subsequent multiwavelength campaigns confirmed the variable nature of these optical histograms and also found that the X-ray and optical emissions were only correlated when Sco X-1 was brighter than about B = 12.6. Models had suggested that the optical emission from this source arose from X-rays reprocessed in an accretion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…This could be suggestive that an additional flux distribution exists at the highest fluxes, thus making the light curve non-stationary and breaking the rmsflux linearity. We note that this could be connected to the trimodal flux distribution previously reported in Sco X-1 (Mook et al 1975;McNamara et al 2003) and/or the extra variability component observed during the high optical luminosity state as seen in Fig. 9.…”
Section: Normal and Flaring Branch Propertiessupporting
confidence: 70%
See 1 more Smart Citation
“…This could be suggestive that an additional flux distribution exists at the highest fluxes, thus making the light curve non-stationary and breaking the rmsflux linearity. We note that this could be connected to the trimodal flux distribution previously reported in Sco X-1 (Mook et al 1975;McNamara et al 2003) and/or the extra variability component observed during the high optical luminosity state as seen in Fig. 9.…”
Section: Normal and Flaring Branch Propertiessupporting
confidence: 70%
“…The optical depth then increases, causing more X-ray photons to be absorbed and re-emitted as optical photons. This phase is associated with an X-ray to optical anti-correlation (McNamara et al 2003). As the source transitions between the NB and the FB, the mass accretion rate exceeds the critical Eddington rate, causing the mass flow to become chaotic with material in the disk flowing both radially inwards and outwards.…”
Section: Introductionmentioning
confidence: 99%
“…The histogram of measured magnitudes (see Fig. 3, on the left) shows three clear states of the Sco X-1 optical emission as previously reported (McNamara et al 2003(McNamara et al , 2005Wright et al 1975).…”
Section: Sco X-1supporting
confidence: 79%
“…Kemp et al 1983). In Sco X–1, this cannot be the case as the accretion disc dominates the optical and NIR and as such any polarized stellar light would be diluted by the light from the disc (McNamara et al 2003; Wachter et al 2006; Russell et al 2007). For GRO J1655−40, the star is large and bright and peaks in the optical (Migliari et al 2007) but the high level of NIR LP and the negative relation between LP and frequency allow us to rule out scattered stellar light as the origin of the NIR LP.Scattering also produces LP that is variable on time‐scales of the orbital period; this has been significantly detected from optical observations of both HMXBs and LMXBs (e.g.…”
Section: Resultsmentioning
confidence: 99%